Emerging Study on Lead‐Free Hybrid Double Perovskite (CH3NH3)2AgInBr6: Potential Material for Energy Conversion between Heat and Electricity. Issue 9 (20th July 2022) - Rani, Upasana; Kamlesh, Peeyush Kumar; Agrawal, Rohit; Shukla, Akash; Singh Verma, Ajay
Abstract : Minimal cost, huge area, high throughput, high performance of photovoltaic panels, prolonged lifespan, and less toxicity are vital aspects when transitioning photovoltaic technology from lab‐scale production to industrial implementations. A new class of materials typically known as hybrid halide double perovskites (HHDPs) has emerged as a possible alternative for the replacement of toxic lead in crystal lattice for realizing lead‐free, stable, and high‐performance perovskite solar cells (PSCs). An ab initio analysis of (MA)2 AgInBr6 HHDP via the WIEN2K code is conducted. It is found that this material has a direct bandgap of 3.85 eV having excellent optical properties in the UV region. The calculated thermodynamic parameters confirm its thermal stability at different temperatures and pressure. Its figure of merit is more than unity at room temperature as well as higher temperature ranges, so this material will be useful in thermoelectric (TE) devices as a TE material. Abstract : Herein, an extensive study of lead‐free hybrid double perovskite (CH3 NH3 )2 AgInBr6 is presented by using density functional theory. Because of their uniqueness and novel properties and their applications in energy conversion between heat and electricity devices, it is promising material for a more stable, cost‐effective, and sustainable hybrids compound for greater effectiveness thermoelectric device manufacturing industries.